PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK INSIDE OUTSIDE CIRCLE (LINGKARAN DALAM LINGKARAN LUAR) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN TATA NAMA SENYAWA DAN PERSAMAAN REAKSI DI KELAS X SMA NEGERI 10 SIAK - Yuniati, Yuniati; Rasmiwetti, Rasmiwetti; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstrack: This study aims to determine the application of Inside Outside Circletechniques can improve student achievement in the subject substance and proceduresequation at the class X SMAN 10 SIAK. This research was conducted at SMAN 10SIAK. Research data retrieval time in July 2011 until July 2014. Study was conductedexperimental research with pretest-posttest research plan. The population in this studywere students of class X SMAN 10 SIAK year 2011-2012. Student sample consisted of 2classes of 4 existing classes which is have the academic skills that are homogeneous,experimental class is class X2 and control class is class X4. The design used in thisstudy was a pretest-posttest design is experimental class and control class.Implementation of the research carried out in two phases, namely Phase Preparation,Implementation Phase. The research instrument is the device that is learning syllabus,lesson plan (RPP) which includes a quiz and evaluation of Student Worksheet. Datacollection instruments in the form of data homogeneity test and pretest-posttestquestions. The data in this study were tested using the statistical test is the t-test. Basedon the research that has been done, it can be concluded that the application ofcooperative learning model application inside outside techniques circle to improvestudent achievement in learning subject substance and procedure sequation at class Xin SMAN 10 SIAK with t count> t table 4,86> 1,67.Key Words: student achievement, cooperative, Inside Outside Circle techniques